2007
DOI: 10.1111/j.1468-5957.2007.02011.x
|View full text |Cite
|
Sign up to set email alerts
|

CEO Ownership and Discretionary Investments

Abstract: This study investigates empirically the relationship between CEO ownership and discretionary investments such as R&D and capital expenditures. We assert that the under-investment problem is high for R&D-intensive projects, while the over-investment problem is high for capital expenditures because of differences in risk between the two types of investments. Building on the linkages between investments and investment-related agency problems, we hypothesize that the relationship between CEO ownership and investme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 70 publications
5
26
0
1
Order By: Relevance
“…However, at high levels of CEO ownership, agency problems increase with ownership because entrenched CEOs with large voting power are less likely to be subject to forces of market discipline (Stulz 1988;McConnell and Servaes 1990;Ghosh et al 2007). Thus, the perceived quality of earnings is predicted to improve with CEO ownership for low ownership levels.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, at high levels of CEO ownership, agency problems increase with ownership because entrenched CEOs with large voting power are less likely to be subject to forces of market discipline (Stulz 1988;McConnell and Servaes 1990;Ghosh et al 2007). Thus, the perceived quality of earnings is predicted to improve with CEO ownership for low ownership levels.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, managers have incentives to implement business strategies or use accounting choices to reduce firms' risk rather than optimize the firms' value (Dechow and Sloan 1991). Managers can reduce the risk of the firm, and thereby reduce the risk of their personal wealth, by (1) reducing R&D expenditure (Kothari et al 2002;Ghosh et al 2007), (2) managing accounting choices to smooth earnings (Trueman and Titman 1988), or (3) through conglomerate mergers (Amihud and Lev 1981).…”
Section: The Linkage Between Earnings Quality and Ceo Equity Ownershipmentioning
confidence: 99%
“…Managers with higher shareholdings have stronger control over the firm, exacerbate the conflicts of interest between shareholders and bondholders, and hence a greater ability to pursue their own private interests (Holderness & Sheehan, 1991;Lennox, 2005). Moreover, managers with higher ownership usually have a stronger incentive to make riskier investment decisions (Chen & Steiner, 1999), and to induce discretionary investments, such as capital expenditures and R&D (Ghosh, Moon, & Tandon, 2007). Since the strength of internal control is highly associated with management philosophy, entrenched managers are likely to design and utilize poorer internal controls, and exploit an MW in order to invest in high-risk projects (Ogneva et al, 2007).…”
Section: Management Ownershipmentioning
confidence: 99%
“…There was another increasing in R&D spending beyond 15% shareholding, in order that a W-shaped relationship existed. Ghosh et al (2007) found that R&D investment rose as CEO shareholding increased below 5%, decreased within the CEO shareholding range of 5% to 25%, and increased again but insignificant beyond 25%. The finding shows that the interest-effect convergence is major within low range of CEO shareholding, while the 5% to 25% shareholding regime demonstrates the entrenchment effect.…”
Section: Ownership Structure and Randdmentioning
confidence: 96%